COVID-19 vaccination decrease the risk of Intensive Care Unit hospitalisation in heart failure patients even in the time of Omicron variant: population based study. (3rd October 2022) - Parenica, J; Jarkovsky, J; Benesova, K; Hlasensky, J; Miklikova, M; Kala, P; Ondrus, T; Lokaj, P; Dusek, L
Abstract: Background: Heart failure (HF) patients, especially those in higher age, are at high risk of severe course of COVID-19. Purpose: The aim of this work was to compare the risk of the necessity of intensive care being provided in the Intensive care units in HF patients with and without COVID-19 vaccination in the time of Omicron variant. Methods: The analysis was done on data from the National Health Information System, which was supplemented with data from the Information System of Infectious Diseases. Results: At the beginning of 2022, we estimate a total of 128, 848 HF patients. Of these, 52.5% were men, mean of age (±SD) was 71.8 (±11.6) years, mean of age of women was 78.2 (±10.7). In January 2022, 560, 886 cases of COVID-19 were diagnosed in the Czech Republic (5, 241.1 cases per 100, 000 population), the mean of the age was 32.5 (±18.3) years. At this time, the Omicron variant prevailed in the Czech Republic. Total 1, 667 COVID-19 cases were HF patients, 56.3% were men. Not vaccinated were 420 patients, vaccinated without booster were 556 patients and vaccinated with booster were 691 patients. The risk of hospitalisation within 14 days from COVID-19 diagnosis was 46.7% (95% CI 41.5%; 51.8%) in not vaccinated group, 37.0% (32.9%; 41.2%) in vaccinated group and 22.6% (19.8; 26.0%) in vaccinated with booster group. The risk of the necessity of intensive care being provided in the Intensive care units was 11.1% (7.7%; 14.5%) in not vaccinated group, 4.7% (2.8%; 6.6%) in vaccinated group and 3.7% (2.0%; 5.4%) in vaccinated with booster group (Figure 1). Conclusion: COVID-19 vaccination decrease the risk of Intensive Care Unit hospitalisation in heart failure patients even in the time of Omicron variant. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): The Ministry of Health of the Czech Republic – conceptual development of research organisation (FNBr, 65269705; funding was given to University Hospital Brno)